Thin Layer Drying Characteristic of Morinda Citrifolia Fruit and Drying Effects on 6 – Methoxy-7-Hydoxy-Coumarin Content - Sulaiman, Rabiha (2004)
This study presents the thin layer drying characteristic of Morinda Citrifolia Linn fruit and drying effects on scopoletin content. The optimum mature stage of M.citrifolia fruit was found to be four months after bud flowering with high scopoletin content of 1.65'gSC/g fresh weight. Thin-layer drying characteristics of M. citrifolia fruit slices were investigated at 50, 60 and 70oC, and air velocity of 0.5, 1.5 and 2.5 m/s. Relative humidity range of 64-85 % was observed. The drying time required to reduce the moisture content from initial average value of 5.25g water/g dry solid (= 84%wet basis ) to a desired final moisture of less than 0.053g water/g dry solid (=5%wet basis) was 6.0h, 3.0h and 1.5h for drying air temperatures of 50oC, 60oC and 70oC respectively. An increase in drying temperatures shortened the drying time. The drying time needed to dry M. citrifolia fruit slices at intermediate moisture content decreased when the air velocities was increased at constant drying temperature. However, different air velocity had no significant difference in overall drying time to achieve equilibrium moisture content at constant temperature. Drying rates for M. citrifolia fruit as affected by drying air temperature and air velocity were determined. The influence of temperature on the drying rate is more pronounced as compared to the influence of the air velocity. From the drying rates it was observed that drying of M. citrifolia fruit slices took place under the falling rate period. The drying data were then fitted to different semi-theoretical models such as diffusion, Lewis and Page models, based on the moisture ratio (MR). The results of analysis showed that Page model gave better predictions than other models, and satisfactorily described the thin-layer drying characteristics of sliced M. citrifolia fruit. Freeze drying and hot air drying experiments were conducted on M.citrifolia fruit. The effect of drying on scopoletin content of M.citrifolia was evaluated. Spectrofluorometer was used for the determination of scopoletin in M.citrifolia fruit. An analysis of variance (ANOVA) revealed that there is no significant difference in scopoletin content obtained from freeze dried and hot air dried sample. This study shows that the remaining scopoletin content after either drying technique is nearly 26% of the initial content